The correlation of Th22 and regulatory T cells with Helicobacter pylori infection in patients with chronic gastritis - Biyu Yao; Xiaoyan Xu; Weijie Liu; Qin Zhang; Wei Wang; Zhiming Huang (Immunity, Inflammation and Disease)
Abstract Objective Helicobacter pylori is planted in the human stomach and is the most common cause of chronic gastritis, which produced specific local and systemic humoral immunity, while the associations of these immune responses and H. pylori in the development of chronic gastritis remain unclear. Methods This study analyzed histology, the number of Th22 and regulatory T (Treg) cells, and the levels of inflammation‐ and gastritis‐related indicators between 22 H. pylori‐infected and 24 non‐H. pylori‐infected chronic gastritis patients by hematoxylin‐eosin staining, enzyme‐linked immunosorbent assay, quantitative reverse transcription PCR, and flow cytometry analysis. Results This study found that the pathological damage degree of gastric mucosa in H. pylori infection patients was more serious. In the H. pylori‐infected patient serum, the gastrin, G‐17, interleukins (IL)‐22, transforming growth factor (TGF)‐β, tumor necrosis factor (TNF)‐α, IL‐4, and IL‐17A levels were notably raised, while the interferon (IFN)‐γ level was inhibited, and in gastric mucosa, and except IFN‐γ, the IL‐22, forkhead box P3 (Foxp3), TNF‐α, IL‐4, and IL‐17A mRNA levels were raised too. The receiver operating characteristic curve analysis indicates serum IL‐22, TGF‐β, TNF‐α, IL‐4, and IL‐17A are suitable for differential diagnosis of H. pylori infection. In addition, in the peripheral blood, the percentages of the IL‐22+ CD4+ and Foxp3+ CD4+ T cells were raised with H. pylori infection. The positive correlation between IL‐22 and Foxp3 mRNA levels and the degree of H. pylori colonization and gastric mucositis by Pearson's correlation analysis. Conclusions Treg and Th22 cells were positively associated with the degree of H. pylori infection and the severity of gastritis. In summary, this study provides an experimental basis for the study of the eradication of H. pylori and the biological mechanism of chronic gastritis.